2016
DOI: 10.1103/physrevlett.117.093901
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Distribution of Phase Singularities in Optical Random Vector Waves

Abstract: Phase singularities are dislocations widely studied in optical fields as well as in other areas of physics. With experiment and theory we show that the vectorial nature of light affects the spatial distribution of phase singularities in random light fields. While in scalar random waves phase singularities exhibit spatial distributions reminiscent of particles in isotropic liquids, in vector fields their distribution for the different vector components becomes anisotropic due to the direct relation between prop… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
47
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 31 publications
(47 citation statements)
references
References 32 publications
0
47
0
Order By: Relevance
“…To gain insight into the spatial distribution of the singularities that underpin the general structure of the flowfield, we determine their pair correlation, which tells us how the points are distributed spatially with respect to each other. For isotropic random waves, it is known that this function is liquid-like [27], which has been verified experimentally [13,18,31]. Fig.…”
Section: Restriction To a 2d Light Fieldmentioning
confidence: 53%
See 1 more Smart Citation
“…To gain insight into the spatial distribution of the singularities that underpin the general structure of the flowfield, we determine their pair correlation, which tells us how the points are distributed spatially with respect to each other. For isotropic random waves, it is known that this function is liquid-like [27], which has been verified experimentally [13,18,31]. Fig.…”
Section: Restriction To a 2d Light Fieldmentioning
confidence: 53%
“…It was recently shown that confinement of light to 2D leads to a fundamental difference in the behaviour of its singularities from those present in the transverse field of a paraxial beam [13,14]. It can be presumed, that such a confinement not only has consequences for singularities in the complex vectorial electromagnetic fields, but also for the singular behaviour exhibited by other physical observables, such as the energy flow.…”
Section: Introductionmentioning
confidence: 99%
“…But vortices are not a peculiarity of superconductors: light's phase swirls around optical vortices, where it is singular [11]. A multitude of these phase singularities arises in random optical fields, one half swirling in opposite direction to the other, so that they can approach respectively to an arbitrarily small distance [12][13][14][15][16]. It is by letting them move that one can observe creation and/or annihilation of such pairs [17][18][19][20][21][22].…”
mentioning
confidence: 99%
“…Figure 1 presents a typical example of our measurements of amplitude and phase of E x . The optical field inside the cavity can be thought of as a random superposition of light waves [28] with transverse electric (TE) polarization [15]. Only the behavior of E x is presented here, without loss of generality as it is representative of the behavior of all in-plane field components [15].…”
mentioning
confidence: 99%
See 1 more Smart Citation